Bioaccumulation of sediment-associated dinonylnaphthalene sulfonates in the freshwater mussel Lampsilis siliquoidea and oligochaete Tubifex tubifex. (February 2021) - Matten, K.J.; Gillis, P.L.; Milani, D.; Parrott, J.L.; Bartlett, A.J.; Toito, J.; Balakrishnan, V.K.; Prosser, R.S.
Abstract: Naphthalene sulfonic acids (NSAs) are used primarily as additives in a wide range of industrial products (e.g., rubber materials, coatings, sealants, fuels, paints). Based on modeled physicochemical properties, NSAs would likely partition into sediments or the tissues of biota in an aquatic system. This study examined the potential for three NSAs, dinonylnaphthalene disulfonic acid (DNDS), barium dinonylnaphthalene sulfonate (BaDNS), and calcium dinonylnaphthalene sulfonate (CaDNS), to accumulate in the tissue of a freshwater mussel ( Lampsilis siliquoidea ) and oligochaete worm ( Tubifex tubifex ). The ability of L. siliquoidea to depurate accumulated chemical was also assessed. Mussels were exposed via sand spiked with CaDNS for 25 d, and then transferred to clean water where their ability to depurate the chemical over an additional 28 d was monitored. Worms were exposed to each of the three NSAs via spiked sediment for 28 d. NSA concentrations were measured separately in gill, foot, and remaining soft tissues (viscera) for mussels and in whole body tissue samples of worms. For L. siliquoidea, the largest concentration of CaDNS was measured in the gill tissue; once removed from CaDNS exposure, mussels were able to depurate up to 87% of the CaDNS from their tissues in 28 days. The biota-sediment accumulation factors (28-d BSAFs) for T. tubifex were 2.8–5.2, 0.53–0.76, and 0.83–1.11 for DNDS, BaDNS, and CaDNS, respectively. For mussel gill and viscera, BCFK values were 14.07 and 16.39, respectively. When BAFK s were calculated using the concentration of CaDNS in sand, they were 1.11 and 1.29 for mussel gill and viscera, respectively. These values are much lower than what would be necessary to classify this chemical as bioaccumulative; however, the BSAFs for DNDS in T. tubifex indicated a potential biomagnification concern if this compound were to occur in the aquatic environment. Highlights: Assessed bioaccumulation of naphthalene sulfonates in two benthic invertebrates. 28-d BSAFs in Tubifex tubifex for BaDNS, CaDNS, and DNDS were 0.76, 1.11, and 5.2 Kinetic BCFs for CaDNS in mussel gill and viscera were 14.07 and 16.39